G178 Low-level laser therapy for children and young people undergoing treatment for cancer. (25th October 2020) - Redman, M; Harris, K; Phillips, B
Abstract : Aim: To assess the efficacy and tolerance/safety of oral low-level laser therapy to prevent or treat oral mucositis in children and young people undergoing chemotherapy. Introduction: Inflammation and ulceration of the oral cavity – known as oral mucositis – can affect up to 80% of children and young people (CYP) undergoing chemotherapy. It can lead to severe oral pain as well as difficulty talking, eating and drinking; it may also lead to treatment cessation. CYP and parents were consulted about their experiences of oral mucositis, and potential future treatment options, through NIHR-funded patient involvement activities, and low-level laser therapy (LLLT) was identified as an approach warranting further exploration. LLLT is a NICE-recommended treatment option for oral mucositis, based mainly on research in adults. It is not currently used for CYP in England or Wales. We determined to conduct an updated systematic review evaluating the evidence for the efficacy and tolerance/safety of LLLT in CYP undergoing treatment for cancer. Methods: Standard systematic review methods were used (protocol registration: PROSPERO CRD42018099772). Two reviewers systematically searched medical databases, contacted authors and reviewed study references. Studies had to include patients with a diagnosis of cancer; use LLLT prophylactically or as a treatment; and, for assessing efficacy, include CYP less than 18 years old, and be a randomised control trial. For the safety/tolerability analysis, all study types and ages were included. Results: 3390 results for initial screening were identified, with 115 full texts assessed for efficacy, and 159 for safety. LLLT is generally well tolerated, and may be effective at treating oral mucositis, but there is uncertainty around the optimal protocol due to the heterogeneity of results. Different protocols were used, adopting various frequencies, dose, timings and wavelengths of LLLT. Conclusion: CYP must not be left behind when new evidence and treatment options become available for adults. LLLT has many ways of administration, and further research is needed to assess the efficacy and appropriate use in CYP. Acknowledgements: We are grateful to NIHR Research Design Service for Yorkshire and the Humber for a grant allowing patient and public involvement.